STUDENTS' PERSPECTIVE ON THE USE OF GOOGLE CLASSROOM IN ENGLISH CLASS - Riyanti, Erni Dewi; Usman, Achmad Sofari (LINGUISTIKA, 2018)
Students have been equipped with technology at their fingertips. They can easily access information anytime and anywhere, as long as the internet connection is available. With the availability of mobile devices in their hands, students can learn better with the aid of Google Classroom. Using Google Classroom can promote their autonomy as this platform helps students to interact, negotiate, and decide the learning process. The study aims to discover students' perspective on the use of Google Classroom in English class among the students of Department of Islamic Economics, Islamic University of Indonesia. The study shows that students enjoy the learning process using this platform. Student-teacher interaction runs pretty well; additionally, feedback on assignments given can also be conducted real time. However, students see that problems, like, unstable internet connection and appropriate instructions on the material?s discussed are points that have to be solved in the coming courses.